Fabrication of mixed matrix membrane containing chlorophyll extracted from spinach for humic acid removal - Azhar, Faiz Hafeez; Harun, Zawati; Hubadillah, Siti Khadijah; Raja Ahmad, Raja Adibah; Sazali, Norsuhailizah; Syamsul Bahri, Syamsutajri; Ibrahim, Siti Aida; Hussin, Rosniza (Elsevier, 2021)
The implementation of the pore-forming agent in the polymeric membrane has been applied for ages in enhancing the characteristics and performance of mixed matrix membrane. In this work, chlorophyll extracted from spinach has been used as an additional pore-forming agent alongside polyethylene glycol (PEG) to improve the polysulfone’s pore structure (PSf) mixed matrix membrane. The effect of chlorophyll was investigated in terms of characteristics and performance of the mixed matrix membrane. As a result, the cross-section morphologies show that the pore structure was enhanced significantly inside the membrane structure for 0.25 wt% chlorophyll concentration, thus resulted in better hydrophilicity, surface roughness, and membrane porosity value. Plus, the permeation and rejection performance was increased drastically due to the pore formation inside the mixed matrix membrane structure. These results prove that the addition of chlorophyll with low concentration managed to improve the characteristics and performance of the fabricated mixed matrix membrane.